2017
DOI: 10.1007/s10144-017-0599-9
|View full text |Cite
|
Sign up to set email alerts
|

Landscape genomics analysis of Achyranthes bidentata reveal adaptive genetic variations are driven by environmental variations relating to ecological habit

Abstract: Knowledge on adaptive genetic variation in response to environmental variation is the key to understanding the adaptive evolution potential of species. China's warm‐temperate zone is an important climatic zone, but only a few landscape genomics studies have been conducted to understand the adaptive evolution of regional vegetation. In this study, natural populations of Achyranthes bidentata Blume were sampled in China's warm‐temperate zone to infer its adaptive evolution using landscape genomics methods. Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Additional important questions are whether, when and how natural selection introduced by environmental variables will affect population genetic structure. The genetic structure of a species is affected by many factors 53,54 . The identification of population genetic structure at the genome level can help provide a comprehensive understanding of the effects of these factors on population genetic structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional important questions are whether, when and how natural selection introduced by environmental variables will affect population genetic structure. The genetic structure of a species is affected by many factors 53,54 . The identification of population genetic structure at the genome level can help provide a comprehensive understanding of the effects of these factors on population genetic structure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the TREEMIX results showed gene flow between the EG and NWG, NG, and SG groups, the current amount of gene flow is not sufficient to eliminate the genetic differentiation caused by ecological isolation. In previous population genetics studies, we have paid more attention to the effects of genetic drift and gene flow on population genetic structure due to the use of neutral markers 53,54 . However, natural selection is also an important force shaping the population genetic structure of species 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Here, the results of LFMM analysis showed that Sr6, Bio6, Bio4, and Wvp1 were associated with the highest numbers of EAL, which suggested that these environmental variables play a major role on the genetic differentiation of P. stenoptera genome. Recent landscape genomic studies have proposed a hypothesis that environmental variables related to ecological habitats of species play key roles in driving adaptive differentiation of species genome [ 2 , 14 , 15 ]. Among the four environmental variables associated with the largest number of adaptive loci, Sr6 was associated with the ecological habitat of “prefered light”, and Bio6 and Wvp1 were associated with the ecological habitat of “warm and humid environment”.…”
Section: Discussionmentioning
confidence: 99%
“…All individuals were genotyped using SCoT markers. Despite its inherent defects lacking DNA sequence information, the SCoT marker has been used for landscape genomic studies because it has the advantages of non-requirement for genomic information, high repeatability, and high throughput [ 2 , 14 , 15 ]. After preliminary screening of the polymorphism and reproducibility of all SCoT primers [ 25 ], nine primers (SCoT5, SCoT9, SCoT16, SCoT18, SCoT25, SCoT27, SCoT30, SCoT31, and SCoT35) were selected for polymerase chain reactions (PCRs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation